Composite Granulated Adsorbents Based on Chitosan and Agricultural Processing Waste for Sewage Treatment - A. Bezdeneznych, L.; V. Kharlamova, O.; M. Shmandiy, V. (International Journal of Engineering and Technology, 2018)
To minimize the impact of industrial enterprises on water objects, a wide variety of adsorbents (based on activated carbon, natural materials, nanomaterials, vegetable waste of agro-industrial complex, etc.) is used. Recently, chitin and chitosan have attracted the attention of scientists due to a number of unique physico-chemical and biological properties (adsorption, antioxidant, radioprotective, immunomodulating, lamina-forming). We have improved the method of obtaining powdered chitosan and established the basic physical and chemical parameters (bulk density, humidity). The method of obtaining chitosan granules and composite materials based on chitosan and modified sunflower husks (MSH) has been further developed by the "drip method". The adsorption properties of powder chitosan, chitosan granules and MSH were studied. It is set that a granular adsorbent has a high adsorbtivity in comparing to the original chitosan. Efficiency of wastewater treatment with the use of chitosan granules and MSH is equally high (up to 98%). The optimum amount of adsorbent for effective cleaning of contaminated water is 1% of its volume. The use of the results of the conducted research allows us to obtain an effective adsorbent for the treatment of industrial waste water. Â